Increasing the Brand Awareness of Grand Nature Residence Real Estate Developer through Facebook Ads - Michelle Gracia Hory; Jusuf Imam Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2026)
This thesis addresses the low brand awareness of Grand Nature Residence, a new real estate project in Sidoarjo. Despite using Instagram and TikTok, the company failed to reach its main target, financially capable young adults, due to a mismatch between platform use and audience behavior. Through semi-structured interviews and questionnaires, the research identified key USPs: strategic location and strong investment potential. To solve this, two Facebook Ads tools were developed: an introductory video and an FAQ post, leveraging Facebook’s precise audience targeting. These tools were crafted to convey the USPs using relevant visuals, language, and narrative. This approach enhances message relevance, exposure, and engagement. By aligning message, medium, and audience, the solution is expected to improve brand visibility and increase buyer interest.